Reconfigurable Chiral Metasurface Absorbers Based on Liquid Crystals - Shengtao Yin (IEEE Photonics Journal, 2018)
We propose a liquid-crystal-based reconfigurable chiral metasurface absorber and numerically investigate its chiro-optical properties. The chiral metasurface absorber consists of a metal-insulator-metal structure with the substrate, which can strongly absorb a circularly polarized wave of one spin state and reflects that of the opposite spin, resulting a strong circular dichroism (CD). A birefringent liquid crystal (LC) is exploited to serve as the insulator layer in the metal-insulator-metal structure. We could then vary the circular state of the incident light by controlling the alignment of the LC molecules, hence inversing the CD. The simulation results show that the CD will change the sign as the LC molecules are realigned from 0° to 90°. The absorption efficiency for the specific circularly polarized wave is larger than 80% and the CD is nearly 70%. The simple and compact design of our proposed chiral metasurface absorber is especially favorable for integration, and such a reconfigurable chiral absorber could find many potential applications in biological detection/sensing, polarimetric imaging, and optical communications.